Answer to Question #241109 in Differential Equations for Joeanna
e ^ (- x) * d * y - (e ^ (- x) * y + y ^ 2) * d * x = 0 .
1
2021-09-23T17:17:09-0400
"e^{-x}dy-(e^{-x}y+y^2)dx=0"
"y'-y=e^xy^2"
"u=y^{1-n}=y^{1-2}=y^{-1}"
"u'=-y^{-2}y'"
"-u'-u=e^x"
"\\mu(x)=e^x"
"e^xu'+e^xu=-e^{2x}"
"(e^xu)'=-e^{2x}" Integrate
"e^xu=\\int(-e^{2x})dx"
"e^xu=-\\dfrac{1}{2}e^{2x}+C_1"
"u=-\\dfrac{1}{2}e^{x}+C_1e^{-x}"
"y(x)=\\dfrac{1}{-\\dfrac{1}{2}e^{x}+C_1e^{-x}}"
"y(x)=\\dfrac{2e^x}{C-e^{2x}}"
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment